Varying magnetic field strength as an effective approach to boost up the plasma signal in laser-induced breakdown spectroscopy. Issue 9 (September 2022) - Hussain, Atif; Iqbal, Syeda Tehreem; Shahbaz, Rana Muhammad; Zafar, Mubeen; Arshad, Arslan Ali; Aslam, Komal; Mukhtar, Maria
Abstract: Externally variable magnetic field was incorporated with the combination of laser induced breakdown spectroscopy (LIBS) to enhance the emission characteristics of aluminum (Al) plasma. Significant emission enhancement of laser induced plasma (LIP) was obtained at different magnetic field strengths, for instance, enhancement factors of about 1.2, 1.3 and 1.4 times were observed at field-strength of 0.4, 0.5 and 0.6 T, respectively. The electron-impact excitation rates and recombination process were increased at higher field-strengths, which led to the higher emission signal due the stronger plasma confinement by the field. The electron number density and electron temperature were measured using the spectroscopic techniques at several delay times. At higher field strengths, both electron density and electron excitation temperature showed an increased trend as compared to the case when No-field was applied. Hence, the research has significance for enhancing the plasma signal which led to improve the LIBS sensitivity. Abstract : Spectroscopy, Excitation, Delay time, Strength, Parameters.